Cost effectiveness of examinations preoperative assessment - Delgado, Bolívar; Chevalier, Nelma; Nicoli, Edgar (Cirugía del Uruguay, 1991)
With regard to a series of 200 ASA class I and 11 patients that underwent current or majar coordination surgery, the authors analyse cost-effectiveness of the so called routine pre-operative paraclinical tests